Research on BER performance of the OAM-SK FSO communication system with wavefront phase correction - Shuang LI; Ping WANG; Tao LIU; Yuting PAN; Wei WANG (Tongxin xuebao)
On the basis of Gerchberg-Saxton (GS) algorithm and angular-spectrum theory, an improved wavefront phase correction algorithm to the Laguerre-Gaussian (LG) beams was proposed for the orbital angular momentum-shift keying (OAM-SK) modulation-based free space optical (FSO) communication system under weak atmospheric turbulence.The light field distributions of the probe beam at transmitter and receiver were regarded as the input of the improved wavefront phase correction algorithm.And the correction phase mask was iteratively calculated to correct the distorted LG beams, thereby alleviating the inter-model crosstalk caused by atmospheric turbulence.Simulation results show that the improved wavefront phase correction algorithm is superior to the conditional GS algorithm.And with the increase of the refractive-index structure parameter, the bit error rate (BER) performance of the OAM-SK FSO communication system is significantly improved.